Exploring New Insights Into Explicit and Implicit Second Language Processing: Event‐Related Potentials Analyzed by Source Attribution. Issue 2 (28th February 2022) - Morgan‐Short, Kara; Finestrat, Irene; Luque, Alicia; Abugaber, David
Abstract: In this exploratory study, we considered the method of combining event‐related potentials (ERPs) and source attributions as a means for examining the explicit or implicit nature of second language (L2) knowledge and processing. We recorded electroencephalograms while L2 Spanish participants judged phrase structure and subject‐verb agreement sentences and provided source attributions—guess, intuition, memory, rule. The participants evidenced above chance performance and anterior P600 effects to the stimuli overall. We examined whether ERPs differed by explicit (memory, rule) or implicit (guess, intuition) source attributions. Mixed‐effects models indicated more positive ERPs when the participants indicated explicit source attributions. Thus, the anterior P600 evidenced in our study seemed to reflect subjectively reported explicit knowledge. Future research will be necessary to reproduce this finding, to understand ERP effects that may be associated with implicit knowledge, and to further explore how ERPs may be triangulated with other types of data to better understand the nature of L2. Abstract :